Next-generation sequencing yields the complete mitochondrial genome of the Capsala pricei Hidalgo, 1959 (Platyhelminthes: Monogenea) from South China Sea. Issue 2 (2nd April 2020) - Yang, Changping; Shan, Binbin; Liu, Yan; Zhao, Yu; Sun, Dianrong
Abstract: The complete mitochondrial genome of the Capsala pricei (Monogenea: Capsalidae) collected from the sailfish ( Istiophorus platypterus ) was sequenced by the next-generation sequencing method. The mitogenome is 13, 851 bp in length, includes 12 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and a control region, with the atp8 gene being absent. The overall content of A + T is 69.26%, which is significantly higher than the C + G content (30.74%). C shows the lowest frequency (13.42%) among four bases. Phylogeography analysis showed a close relationship between the genus Capsala and Neobenedenia with high bootstrap value supported.